Treatment of menopausal symptoms by an extract from the roots of rhapontic rhubarb: the role of estrogen receptors - Zierau Oliver; Papke Anja; Vollmer Günter (BMC, 2010)
Abstract A dry extract from the roots of rhapontic rhubarb (extract Rheum rhaponticum (L.); ERr) has been commercially available in Germany for over two decades to treat menopausal symptoms. However, the molecular basis of its clinical effectiveness remains obscure. This article reviews the in vitro and in vivo data of its estrogenic actions, particularly those mediated by estrogen receptor-β (ERβ).